Well, darling, if we're talking math, P squared plus P squared equals 2P squared. It's as simple as that. So, next time you're trying to impress someone with your algebra skills, just remember this little gem.
p2 + 9p + 18/ p + 6(p + 6)(p + 3)/ p + 6(p + 6)(p + 3)/ p + 6p + 3
When you divide p cubed by p squared, you are essentially dividing p to the power of 3 by p to the power of 2. This simplifies to p^(3-2), which equals p^1. Therefore, the result of p cubed divided by p squared is p.
p^2 x p^2 = p^4 p^2 + p^2 = 2p^2
p2-2p = p(p-2) when factored
The value of p is 1.4
(p+9)(p+6)
-2p squared
p2 + 9p + 18/ p + 6(p + 6)(p + 3)/ p + 6(p + 6)(p + 3)/ p + 6p + 3
p2 + p2 + p3 = 2p2 + p3 because you can add the two variables that match, while you leave the different variable alone.
s = p^2 - 5 *also, p = sqrt (s+5)
P squared = P*P. When divided by P, the equation becomes (P*P/P, and the answer is "P".
answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}
p2 X p2 = p4or p X p X p X p = p4
p^2(p squared)
Oh, dude, you're hitting me with some math here! So, "p times p squared" is basically p multiplied by p squared, which is p to the power of 2. When you multiply p by p squared, you're essentially multiplying p by p to the power of 2, which gives you p to the power of 3. So, the answer is p cubed. Math can be fun... sometimes.
When you divide p cubed by p squared, you are essentially dividing p to the power of 3 by p to the power of 2. This simplifies to p^(3-2), which equals p^1. Therefore, the result of p cubed divided by p squared is p.
p2 = 2p + 15 p2 - 2p - 15 = 0 (p - 5)*(p + 3) = 0 so p - 5 = 0 or p + 3 = 0 so p = 5 or p = -3